Identifying Cell‐Type‐Specific Metabolic Signatures Using Transcriptome and Proteome Analyses. Issue 9 (13th September 2021) - Gebert, Nadja; Rahman, Shahadat; Lewis, Caroline A.; Ori, Alessandro; Cheng, Chia‐Wei
Abstract: Studies in various tissues have revealed a central role of metabolic pathways in regulating adult stem cell function in tissue regeneration and tumor initiation. The unique metabolic dependences or preferences of adult stem cells, therefore, are emerging as a new category of therapeutic target. Recently, advanced methods including high‐resolution metabolomics, proteomics, and transcriptomics have been developed to address the growing interest in stem cell metabolism. A practical framework integrating the omics analyses is needed to systematically perform metabolic characterization in a cell‐type‐specific manner. Here, we leverage recent advances in transcriptomics and proteomics research to identify cell‐type‐specific metabolic features by reconstructing cell identity using genes and the encoded enzymes involved in major metabolic pathways. We provide protocols for cell isolation, transcriptome and proteome analyses, and metabolite profiling and measurement. The workflow for mapping cell‐type‐specific metabolic signatures presented here, although initially developed for intestinal crypt cells, can be easily implemented for cell populations in other tissues, and is highly compatible with most public datasets. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Intestinal crypt isolation and cell population purification Basic Protocol 2 : Transcriptome analyses for cell‐type‐specific metabolic gene expression Basic Protocol 3 : Proteome analyses for cell‐type‐specific metabolic enzyme levels Basic Protocol 4 : Metabolite profiling and measurement